Tipologi Zona Desa-Kota dengan Pendekatan Transek di Lasem , Kabupaten Rembang - Laras Sita Permata Puri; Rina Kurniati (Teknik PWK (Perencanaan Wilayah Kota), 2020)
Lasem is the one of sub-district capital in Rembang regency which is developing in a strategic location because it is traversed by regional transportation route, Pantura Route. It affects on land use conversion and the pattern of physical development that spreads along the regional route so as it forms the physical characteristic of Lasem. The phenomenon is indicated by the crisis of urban form dan urban sprawl in Lasem. Transect planning is an approach which aims to create an immersive environment and integrate rural-to-urban continuum by promoting sustainable urban form and providing the logical pattern of  development from rural-to-urban, vice versa. This article aims to identify the transect from rural-to-urban continuum in Lasem by identify elements of urban form such as density, land use, building function, building layout (height building configuration), and transportation infrastructure. This research is analysed by scoring process and spatial analysis based on GIS, so that it results the transect from rural-to-urban in Lasem is discrete because the elements of urban form are diverse and complex. The research is expected can  provide recommendations to the Government in controlling spatial uses in Lasem which accordances to the intensity of the location (rural or urban).